ANALISIS RISIKO DAN PENGEMBALIAN HASIL TERHADAP PEMBIAYAAN MUDARABAH PADA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) - Abrar Amri; Yuci Cindia Oviza (Universitas Teuku Umar, 2020)
This study examines the risk and return that effect mudarabah financing at Islamic Rural Banks. The study uses the Value at Risk (VaR) method to measure risk and for Return using the Risk Adjusted Return on Capital (RAROC) method. The data used are secondary data were gathered from the 2016-2018 Monthly from Financial Reports that published on the Financial Services Authority website. The results of the analysis show that risk affects mudarabah financing, whereas the return of results does not affect mudarabah financing. Meanwhile, simultaneously it shows that the risk and return affect mudarabah financing financing at Islamic Rural Banks